Physical training induced resting bradycardia and its association with cardiac autonomic nervous activities. - Alom, MM; Bhuiyan, NI; Hossain, MM; Hoque, MF; Rozario, RJ; Nessa, W (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):665-70 The abstract of this article is available on the PubMed website